The Impact of the COVID-19 Pandemic on the Construc􀆟 on Industry in the Philippines - Serrano, Melisa R.; Castillo, Rolly Czar Joseph (Philippine Journal of Labor and Industrial Relations; Vol 37 (2020): Philippine Journal of Labor and Industrial Relations, 2023)
Construction emerged as a casualty of the COVID-19 pandemic and the lockdowns imposed by the Philippine government aimed at curbing the community transmission of the virus. Construction activities declined by 34 percent in the second quarter of 2020, and more than half of employment losses in industrial activities came from job losses in construction. The government rolled out several programs that provided income replacement, wage subsidy, and direct cash transfers to affected and displaced workers. However, only a few received financial support from the national and local governments. Meanwhile, construction companies are still reeling from the health and economic impacts of the pandemic. Many are still operating at reduced capacity as they face reduction in the size of their labor force due to a host of factors. Using a uniquely designed questionnaire, the study explored how the COVID-19 pandemic and the lockdowns affected jobs, incomes, and working conditions of workers employed in selected construction projects in Metro Manila, and the forms of support they received during the pandemic. The survey findings suggest that the lockdowns resulted in work suspension for a majority of the survey respondents. Those who were able to return to work when lockdowns eased experienced reduced earnings. On the bright side, worker safety during the pandemic appears to be a top priority among the construction projects covered by the survey. Nonetheless, more needs to be done in terms of establishing occupational safety and health (OSH) committees in many workplaces and in instituting worker representation in these committees. Finally, the pandemic may have exacerbated the difficulties faced by trade unions in organizing workers in the construction industry, but the massive infrastructure programs that have been included in the Philippine government’s COVID-19 economic recovery program makes the industry a greenfield for organizing. The survey disclosed that construction workers are willing to be organized into various forms of worker organizations for the protection of their rights and security at work, especially during a pandemic.